Exploring climate change perceptions, climate trends and the level of knowledge on the subject in farmers from Guasave, Mexico - Ahumada-Cervantes, Ramiro; González-Márquez, Luis Carlos; Martínez-Álvarez, Iván Guadalupe; Rodríguez-Gallegos, Hugo Benigno (GeoJournal, 2023)
Climate change has adverse consequences for socioeconomic activities such as agriculture, as it can affect crop yields and production costs. Farmers' adaptation to the impacts caused by this phenomenon may be limited because they do not perceive the problem, have limited knowledge of the subject or by lack of willingness to change certain behaviors. In this way, the objectives of this research were to know the farmers’ perception of climate change, if what they perceive match with the trends of the climate records of temperature and rainfall, as well as to assess the level of knowledge that farmers have about climate change. This with the purpose of laying the foundations for the adaptation to climate change in the municipality of Guasave, Sinaloa, Mexico. A structured survey was applied in 1111 agricultural households selected at random and proportionally in 153 communities. The results show that 43% of respondents have an acceptable level of knowledge about climate change and that 89.4% perceive changes in climate, mainly in temperature, but this is not statistically corroborated with climate records. Likewise, 52.2% attribute the problem to anthropogenic causes, mainly pollution. They point out that this phenomenon could decrease agricultural production; generate higher electricity consumption and a higher incidence of diseases. The vast majority of respondents is willing to implement actions to minimize the problem and its impact on the region; however, an awareness-raising program is needed about the problem (causes, impacts, and the way to face it).